Social policy and welfare pluralism selected writings of Robert Pinker - Pinker, Robert 1931- (Policy Press, 2017)
This book presents the first collection of Robert Pinker's influential essays in one edited volume, discussing the key concepts underpinning the study of social policy and the ways in which welfare theories and ideologies together with public expectations have shaped the political processes of policy making